Підвищення надійності підшипників ковзання вібронакатуванням - Паніна, Валерія Валеріївна; Панина, Валерия Валерьевна; Panina, Valeriia; Дашивець, Галина Іванівна; Дашивец, Галина Ивановна; Dashyvets, Halyna; Бондар, Андрій Миколайович; Бондарь, Андрей Николаевич; Bondar, Andrii; Новик, Олексій Юлійович; Новик, Алексей Юльевич; Novyk, Oleksii (ТДАТУ, 2020)
UK: Поверхневий шар матеріалу деталей спряжень надає безпосередній вплив на надійність та довговічність підшипників ковзання. При ремонті або виготовленні деталей підшипників ковзання, зокрема втулок, пропонується використовувати один з видів поверхнево-пластичної обробки – вібронакатування. В роботі: - надані відомості про мікрорельєф поверхонь, утворених при різних способах кінцевої обробки та переваги поверхнево-пластичної обробки; - проведено аналіз наукової літератури та надані переваги вібронакатування над іншими способами обробки поверхні; - надані відомості про сутність процесу вібронакатування, обладнання, що використовується, вплив режимів вібронакатування на характер отриманого мікрорельєфу; - запропоновано систему мікронерівностей, що дозволить збільшити зносостійкість робочої поверхні втулки, та маслоутримуючу здатність; - пропонується конструкція приладу для вібронакатування внутришньої поверхні втулки; - надані рекомендації з вібронакатування втулок; - розроблена номограма для визначення режимів вібронакатування робочих поверхонь втулок підшипників ковзання. RU: Поверхностный слой материала деталей сопряжений оказывает непосредственное влияние на надежность и долговечность подшипников скольжения. Предлагается использовать при ремонте или изготовлении деталей подшипников скольжения, в частности втулок, один из видов поверхностнопластической обработки - вибронакатывание. В работе: - представлены сведения о микрорельефе поверхностей, образованном при разных способах конечной обработки и преимущества поверхностно-пластичной обработки и проведен анализ научной литературы и оказано предпочтение вибронакатыванию по сравнению с другими способами обработки поверхности и - представлены сведения о сущности процесса вибронакатывания, используемого оборудования, влиянии режимов вибронакатывания на характер полученного микрорельефа; - предложена система микронеровностей, которая позволит увеличить износостойкость рабочей поверхности втулки и маслоудерживающую способность; - предлагается конструкция прибора для вибронакатывания внутренней поверхности втулки и предоставлены рекомендации по вибронакатыванию втулок; - разработана номограмма для определения режимов вибронакатывания рабочих поверхностей втулок подшипников скольжения. EN: The surface layer of the material of the mating parts has a direct impact on the reliability and durability of the plain bearings. In the work, it is proposed to use one of the types of surface-plastic processing – vibron rolling – in the repair or manufacture of parts of sliding bearings, in particular bushings. In the process of vibrating, the surface layer of the workpiece is machined along a helical line by a ball moving reciprocally and forming a sine wave. As a result, grooves of a certain shape and micro-relief, several microns deep, are extruded on the surface. The following has been done in the work: - рrovided information about the surface microrelief formed by different methods of final processing and the advantages of surface-plastic processing; - an analysis of the scientific literature on this topic was carried out, and preferences were given over the other methods of surface treatment; - рrovides information about the essence of the process of rolling, the equipment that is used, the effect of the rolling modes on the nature of the obtained microrelief; - a micro-irregular system is proposed, which will increase the wear resistance of the working surface of the sleeve, and oil-holding ability; - a device design for vibro-rolling the inner surface of the sleeve is proposed; - recommendations on vibro-rolling of bushings are provided; - A nomogram has been developed for determining the modes of vibration rolling of the working surfaces of sleeve bearings. For processing 60% of the inner surface of the sleeve bearing sliding surface plastic deformation, the treatment modes should be as follows: diameter of a ball of a vibrating roller - 3 mm; speed of the workpiece - 200 min-1; longitudinal feed of the machine - 3 mm / turn; the width of the rolled tape - 1 mm.
Повышение надежности подшипников скольжения вибронакатыванием
Improving the reliability of bearings of sliding vibration pumps
Keywords: поверхневий шар; мікрорельєф; вібронакатування; зміцнення; втулка; установка; режими; номограма; поверхностный слой; микрорельеф; вибронакатывание; упрочнение; режим; номограмма; surface layer; micro-relief; vibrating; strengthening; bushing; installation; modes; nomogram